Succinobucol‐eluting stents increase neointimal thickening and peri‐strut inflammation in a porcine coronary model. Issue 4 (8th November 2012) - Watt, Jonathan; Kennedy, Simon; McCormick, Christopher; Agbani, Ejaife O.; McPhaden, Allan; Mullen, Alexander; Czudaj, Peter; Behnisch, Boris; Wadsworth, Roger M.; Oldroyd, Keith G.
<x xml:space="preserve">Abstract</x> Objective The aim of this study was to assess the efficacy of stent‐based delivery of succinobucol alone and in combination with rapamycin in a porcine coronary model. Background: Current drugs and polymers used to coat coronary stents remain suboptimal in terms of long term efficacy and safety. Succinobucol is a novel derivative of probucol with improved antioxidant and anti‐inflammatory properties. Methods Polymer‐free Yukon stents were coated with 1% succinobucol (SucES), 2% rapamycin (RES), or 1% succinobucol plus 2% rapamycin solutions (SucRES) and compared with a bare metal stent (BMS). Results The in vivo release profile of SucES indicated drug release up to 28 days (60% drug released at 7 days); 41 stents (BMS, n = 11; SucES, n =10; RES, n = 10; SucRES, n = 10) were implanted in the coronary arteries of 17 pigs. After 28 days, mean neointimal thickness was 0.31 ± 0.14 mm for BMS, 0.51 ± 0.14 mm for SucES, 0.19 ± 0.11 mm for RES, and 0.36 ± 0.17 mm for SucRES (P < 0.05 for SucES vs. BMS). SucES increased inflammation and fibrin deposition compared with BMS (P < 0.05), whereas RES reduced inflammation compared with BMS (P < 0.05). Conclusion In this model, stent‐based delivery of 1% succinobucol using a polymer‐free stent platform increased neointimal formation and inflammation following coronary stenting. © 2012 Wiley Periodicals, Inc.